Use of psychoactive substances among teens and young people in schools in Benin: from experimentation to dependence - Kougblenou, A. Odile; Sossa, Charles; Adounkpe, Ferdinand M.; Bio Sya, A. Assad; Agbanlinsou, C. Arnaud; Akpi, Eric Ayédjo; Meliho, Pierre Codjo; Kpatchavi, Codjo Adolphe; Houinato, Dismand; Laleye, Anatole (International Journal Of Community Medicine And Public Health, 2022)
Background: The use of psychoactive substances among adolescents and young people in schools in Benin is growing despite its consequences on their health. This article analysed this practice, identified the types of use and their determinants along the consumption trajectory. Methods: It was mixed, transversal study and involved 617 students from high schools and colleges in Cotonou and Parakou in 2020. Sampling was in two-degree clusters. 65 students were drawn by reasoned choice and snowball for qualitative interviews. Data processing was done with SPSS software and content analysis. Results: The results show that there was a diversity of substances available, accessible and used by targets in the last three months prior to the survey. Three types of use were identified: experimental use, determined by curiosity (48.14%), the quest for generational identity (25.45%) and sociability (34.20%); misuse, influenced by the quest for physical and sexual performance (17.83%), intellectual performance (28.85%) and peer pressure (22.04%) and dependent use, determined by the precocity of experimentation (69.04%), family type (33.60%) and the relaxation of societal values. Conclusions: Adolescents living in abusive and dependent uses are particularly vulnerable in terms of health and social. This requires a preventive approach based on education in societal values, the fight against the availability of these substances and the early management of cases of dependence.